NANOPLEX: A REVIEW OF NANOTECHNOLOGY APPROACH FOR SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT - Kasar, Poonam Madhukar; Kale, Kalyani Sundarrao; Phadtare, Dipti Ganesh (International Journal of Current Pharmaceutical Research, 2018)
The use of nanotechnology based on the development and fabrication of nanostructures is one approach that has been employed to overcome the challenges involved with conventional drug delivery systems. Formulating Nanoplex is the new trend in nanotechnology. Nanoplex means drug nanoparticle complex with the oppositely charged polyelectrolyte. In this technique, the cationic or anionic drug is reacted with an oppositely charged polyelectrolyte to form a complex. Compared with other nanostructures, the yield of Nanoplex is greater and the complexation efficiency is better. The nanoplex formed shows improved solubility and dissolution rate compared to raw drug crystals. Nanoplex formulation is characterized through the production yield, complexation efficiency, drug loading, particle size and zeta potential using scanning electron microscopy, differential scanning calorimetry, X-ray diffraction and dialysis studies. Nanoplex have wide-ranging applications in different fields such as cancer therapy, gene-drug delivery, drug delivery to the brain and protein and peptide drug delivery.